Pengaruh Dukungan Manajemen Puncak, Partisipasi Pemakai, Pelatihan dan Pendidikan terhadap Kepuasan Pemakai Sistem Informasi Akuntansi (Studi Kasus pada LPK Monarch Bali) - Ni Putu Ayu Aryaningsih; Tiara Kusuma Dewi; Komang Krishna Yogantara (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
Accounting Information System is a system designed to collect and display accounting information so that accountants and company executives can make the right decisions. These systems are considered an important component of financial offices around the world, most of which are software-based and can be implemented as part of a company's information technology solution. This research aims to determine the influence of top management support variables, user participation, training and education programs on user satisfaction of accounting information systems. The research method used is a quantitative research method with primary data obtained from questionnaire data which is measured using a Likert scale. This research was conducted at LPK Monarch Bali. The sample in this study amounted to 40 samples. Samples were taken from the population based on a purposive sampling approach. Furthermore, after the data was collected, data analysis was carried out in the form of descriptive analysis and statistical analysis. The results of this research state that top management support has a positive and significant effect on the satisfaction of users of the Monarch Bali job training institute (LPK) accounting information system. The participation of users of the accounting information system has a positive and significant effect on the satisfaction of users of the accounting information system of the Monarch Bali Job Training Institute (LPK). Training and education programs have a positive and significant effect on user satisfaction of the Monarch Bali job training institute (LPK) accounting information system.